Developmental apraxia of speech: I. descriptive and theoretical perspectives. - Shriberg LD; Aram DM; Kwiatkowski J (Journal of Speech, Language & Hearing Research, 1997)
Developmental apraxia of speech (DAS) is a putative diagnostic category for children whose speech errors presumedly (a) differ from the errors of children with developmental speech delay (SD) and (b) resemble the errors of adults with acquired apraxia of speech. The studies reported in this series (Shriberg, Aram, & Kwiatkowski, 1997a, 1997b) concern both premises, with primary focus on the first--that children with DAS can be differentiated from children with SD on the basis of one or more reliable differences in their speech error profiles. Immediate goals are to identify a diagnostic marker for DAS and to consider implications for research and clinical practice. A long-term goal is to identify the phenotype marker for DAS, on the assumption that it may be a genetically transmitted disorder. This first paper reviews relevant descriptive and theoretical perspectives. Findings from a local ascertainment study support the clinical functionality of the term suspected DAS.